Fulton Motel on Huntington Avenue, ca. 1959 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the Fulton Motel, located on Huntington Avenue. A street light and parking meters line the sidewalk in front of the building. 7 3/4 x 7 1/2, 9 7/8 x 7 15/16 overall Photographs